An Unusual Inverted Talar Neck Fracture–Dislocation - Brent Kokubun; Motasem Refaat (Case Reports in Orthopedics)
Talar neck fractures occur on a continuum of injury severity. Hawkins classification, later modified by Canale, is the gold standard method of describing talar neck fractures by the degree of dislocation. It has proven to be clinically relevant in predicting risk of osteonecrosis. Despite its merits, talar neck fractures present on a wide spectrum of involvement of the body and neck, dislocation, and concomitant injuries, making every situation a challenge in treatment. We present a unique case of a talar neck fracture in which the talar dome had dislocated and inverted 180°, which is not described in the widely used Hawkins classification. We recommend urgent open reduction, low threshold for use of a transcalcaneal traction pin and dual incisions, and guarded prognosis of osteonecrosis and posttraumatic arthritis.